Masters : book arts : major works by leading artists - Wallace, Eileen; Hale, Julie; Lark Books (New York : Lark Books, 2011)
This collection in the popular Masters series, chosen and introduced by a top curator, shows field-defining work from 43 master book artists. The selections demonstrate conceptual, aesthetic, and technical excellence, as well as incredible beauty. Brief comments from the artists about their work, careers, and philosophies accompany the stunning images of their most innovative achievements. - Publisher.
The Masters: --Julie Chen --Claire Van Vliet --Brian Dettmer --Margaret Couch Cogswell --Shanna Leino --Susan King --Barbara Tetenbaum --Harry Reese and Sandra Liddell Reese --Sarah Bryant --Susan Goethel Campbell --Bonnie Stahlecker --Karen Kunc --Peter Madden --Wilber Schilling --Hedi Kyle --Ines von Ketelhodt and Peter Malutzki --Ad{grave}ele Outteridge --Ian Boyden --Timothy Ely --Jody Alexander --Macy Chadwick --Ken Botnick --Genie Shank --Julie Leonard --Andrea Dezs{uml}o --Sarah Bodman --Daniel Essig --Karen Hanmer --Keith Smith --Barbara Mauriello --Veronika Sch{uml}apers --Daniela Deeg and Cynthia Lollis --Lynne Avadenka --Robin Price --Elsi Vassdal Ellis --Béatrice Coron --Pati Scobey --Daniel Kelm --Laura Wait --Julie Fremuth.
Includes index.
Keywords: Artists' books -- Themes, motives